Formulasi dan uji aktivitas antibakteri sediaan salep kombinasi ekstrak etanol daun Sirih dan Binahong terhadap Staphylococcus aureus - Qurratu Aini; Rasidah Rasidah (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Betel leaf (Piper betle L) and Binahong leaf (Anredera cordifolia (Tenor) Steenis) are plants that are often used in traditional medicine. Both of these leaves are efficacious as antibacterials.Objective: This study aimed to determine the stability and antibacterial activity of the combination ointment of Betel leaf extract and Binahong leaf and compare ointment preparations that best inhibit Staphylococcus aureus.Methods: This research was experimentally conducted in the laboratory of the Faculty of Mathematics and Natural Sciences, Syiah Kuala University, and the laboratory of the Department of Pharmacy, Poltekkes, Ministry of Health, Aceh, in January 2023. Ointment formulation combination of Betel leaf extract and Binahong leaf in the ratio of (1:1), (2:1), and (1:2). Ointment stability tests include organoleptic tests, homogeneity, pH, dispersion, and irritation tests performed on days 1 and 30. Antibacterial activity test using the pitting method. Data analysis was done descriptively and followed by an ANOVA statistical test.Result: The organoleptic test results obtained no changes in the ointment preparation after the storage period. The results of the homogeneity test show that the resulting ointment preparation has homogeneous properties. The results of the pH evaluation of the ointment in the range of 4,5-4,8. The results of the evaluation of the dispersion of the ointment by 5,1-5,5 cm. The results of the irritation evaluation showed the absence of irritation on the skin after the ointment was applied. The results of the antibacterial activity test of the ointment preparation are known to be the inhibitory zone of the combination ointment of Betel leaf extract and Binahong leaf (2: 1) of 28,56 mm and is significantly different from all treatments in inhibiting Staphylococcus aureus.Conclusion: The combination ointment of Betel leaf ethanol extract and Binahong leaf meets the criteria of good ointment stability and can inhibit the growth of Staphylococcus aureus with powerful inhibitory power category